Differential effects of acute and chronic treatment with the flavonoid chrysin on anxiety-like behavior and Fos immunoreactivity in the lateral septal nucleus in rats - Germán-Ponciano León Jesús; Puga-Olguín Abraham; De Jesús Rovirosa-Hernández María; Caba Mario; Meza Enrique; Rodríguez-Landa Juan Francisco (Acta Pharmaceutica)
The aim of this study was to compare the effects of acute (a single injection) and chronic (21 consecutive days) treatments with chrysin 2, 4, and 8 μmol kg−1 on anxiety-like behavior and Fos immunoreactivity in the lateral septum nucleus (LSN), a structure that is involved in the regulation of anxiety, in male Wistar rats. These effects were compared with the clinically effective anxiolytic diazepam 7 μmol kg−1. The results showed that acute, but not chronic treatment, with 4 μmol kg−1 chrysin exerted anxiolytic- and anti- depressant-like effects with these effects being similar to that of diazepam. Also, none of the above-mentioned treatments did alter Fos immunoreactivity in the LSN, but a tendency towards the reduction of this variable was detected with chrysin 4 μmol kg−1 and diazepam 7 μmol kg−1. Altogether, results suggest that chrysin exerts anxiolytic-like effects, however, it can produce pharmacological tolerance after repeated use, similar to benzodiazepines.